2021 18th International Multi-Conference on Systems, Signals &Amp; Devices (SSD) 2021
DOI: 10.1109/ssd52085.2021.9429345
|View full text |Cite
|
Sign up to set email alerts
|

On the Early Detection of COVID19 using Advanced Machine Learning Techniques: A Review

Abstract: The outbreak of the new coronavirus (COVID19), has caused devastating effects and was declared as a major pandemic by the World Health Organization (WHO). Apart from knowing the main causes, it's very important to timely diagnose the virus in an individual, so that treatment and isolation (if needed) can start as early as possible and spread of the virus is contained among the healthy people. In this research, we discuss various machine learning (ML) and deep learning (DL) approaches that have been proposed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The paper's machine learning section examines works by researchers who have utilized machine learning techniques to detect covid 19. SVM appeared to be the most widely used technique, as it was utilized in [75,77,78,96,99,101,119]. Many articles [78,95,98,99,101,119] used KNN because it produced good results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paper's machine learning section examines works by researchers who have utilized machine learning techniques to detect covid 19. SVM appeared to be the most widely used technique, as it was utilized in [75,77,78,96,99,101,119]. Many articles [78,95,98,99,101,119] used KNN because it produced good results.…”
Section: Discussionmentioning
confidence: 99%
“…SVM appeared to be the most widely used technique, as it was utilized in [75,77,78,96,99,101,119]. Many articles [78,95,98,99,101,119] used KNN because it produced good results. In addition, we applied our own algorithm to predict COVID-19 in Lung CT scan pictures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To accelerate the detection and classification of CAP and COVID-19 in clinical settings, artificial intelligence (AI) algorithms (Wang et al, 2022;Siddiqui et al, 2021;Mondal et al, 2021;Hussain et al, 2022) have recently been introduced and have shown great promise, which can reduce the burden of expert radiologists/clinicians to detect and assess the severity of pneumonia. Several studies recently reviewed these AI techniques used in COVID-19 detection and analysis in ultrasound (Zhao and Lediju Bell, 2022;Wang et al, 2022;Alzubaidi et al, 2021;Siddiqui et al, 2021;Mondal et al, 2021;Liu, 2021;Gudigar et al, 2021;Ulhaq et al, 2020). Most of these review works have been performed between late 2019 and early 2022 and mainly focused on discussing AI techniques used in different ultrasound-based COVID-19 studies.…”
Section: Ai For Ultrasound-based Covid-2019 Managementmentioning
confidence: 99%
“…To accelerate the detection and classification of CAP and COVID-19 in clinical settings, artificial intelligence (AI) algorithms [4,[25][26][27] have recently been introduced and have shown great promise, which may lessen the burden of expert radiologists/clinicians to detect and assess the severity of pneumonia. Several studies recently reviewed these AI techniques used in COVID-19 detection and analysis in ultrasound [4,25,26,[28][29][30][31][32]. Most of these review works have been performed between late 2019 and early 2022 and mainly focused on discussing AI techniques used in different ultrasound-based COVID-19 studies.…”
Section: Ai For Ultrasound-based Covid-2019 Managementmentioning
confidence: 99%